History of the Graeco-Latin fable - Adrados, Francisco Rodríguez, 1922- (Mnemosyne, Supplements, 1999)
This is the second of three volumes covering the long history of the fable from Sumer to the present day. Historical evidence reaching as far back as Antiquity, supports the study of more than 500 works considered to be fables.